Rāshṭrakūṭoṃ (Rāṭhoṛoṃ) kā itihāsa : prārambha se lekara Rāva Sīhājī ke Māravāṛa meṃ āne taka - Reu, Viśveśvaranātha (SAMP early 20th-century Indian books project, 1934)
On the history of the Rashtrakutas, rulers of India during 324 B.C.-1000 A.D.